2015
DOI: 10.1111/epi.12988
|View full text |Cite
|
Sign up to set email alerts
|

“A journey around the world”: Parent narratives of the journey to pediatric resective epilepsy surgery and beyond

Abstract: OBJECTIVE Although shorter time to pediatric resective epilepsy surgery is strongly associated with greater disease severity, other non-clinical diagnostic and sociodemographic factors also play a role. We aimed to examine parent-reported barriers to timely receipt of pediatric epilepsy surgery. METHODS We conducted 37 interviews of parents of children who previously had resective epilepsy surgery at UCLA (2006–2011). Interviews were audio-recorded, transcribed and systematically coded using thematic analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 38 publications
2
61
0
Order By: Relevance
“…Throughout their decision-making, parents identified additional information and emotional support needs. This finding confirms those of other studies [2,9] in which patients and parents of children with intractable epilepsy describe receiving inadequate information regarding surgical treatment. It is already known that information helps to alleviate anxiety, and positively influences acceptance of treatment options including surgery [1,7] and that physicians play a key role in influencing parents to accept surgery for their child with epilepsy through the provision of information [1,2].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Throughout their decision-making, parents identified additional information and emotional support needs. This finding confirms those of other studies [2,9] in which patients and parents of children with intractable epilepsy describe receiving inadequate information regarding surgical treatment. It is already known that information helps to alleviate anxiety, and positively influences acceptance of treatment options including surgery [1,7] and that physicians play a key role in influencing parents to accept surgery for their child with epilepsy through the provision of information [1,2].…”
Section: Discussionsupporting
confidence: 90%
“…Finally, studies show that parents who have been through the process of considering and accepting surgical intervention for their epileptic child would be willing to provide decisional support to other parents, as a way of 'giving back' to the service [9]. Parents in this study also suggested that they would be happy to share their experiences with others in similar situations.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…31,[40][41][42][43][44][45][46][47][48] Moreover, while the social milestones examined here, including divorce and fractured family dynamics, are common across any population, what we have described are changes in social trajectories that patients attribute to the process of undergoing surgery. In such research, a specific "control" group, healthy or medical, is typically not relevant.…”
Section: Strengths and Limitationsmentioning
confidence: 99%